SINTESIS POLY(P-PHENYLENE VINYLENE) SEBAGAI MATERIAL POLIMER ELEKTRONIK - Soni Setiadji (JURNAL ISTEK, 2013)
In this research has been done synthesis of PPV poly (p-phenylene vinylene) and its characterization. PPV synthesis was done by using method of precursor route that including steps of monomerization, PPV precursor polymerization and thermal conversion. Thermal conversion was done in nitrogen gas system with a temperature 300oC for 12 hours. From FT-IR characterization of monomerization given bonds of C-S, C-Cl, C-H, and C= C which indicates the monomer is sulfonium salt. From FT-IR characterization of PPV precursor polymerization follows bonds of C-H aliphatic, C-H trans-vinylene, C-H p-phenylene, C-Cl and C-S which indicates structure of precursor has been formed. However, the result of FT-IR to identify PPV polymer still found C-Cl bond and carbonyl which it showing PPV polymer is not excellent. From UV-Vis characterization of PPV shows it has a maximum absorption peak at 312 nm. PPV precursor of absorption peak is longer than PPV, that has value 326 nm.